Greener analytical method for the determination of copper(II) in wastewater by micro flow system with optical sensor - Tapparath Leelasattarathkul (2018)
Greener analytical method using micro flow system for the determination of Cu(II) in wastewater samples was designed and investigated. The micro flow system consisted of a planar glass chip with poly(dimethylsiloxane) (PDMS) top plate and fixed with fiber optic probe as optical sensor for monitoring of Cu(II) that reacted with 2-carboxy-2′-hydroxy-5′-sulfoformazyl benzene (zincon) on the chip at 605 nm. This design gave a satisfied sensitivity with a linear calibration graph over the range of 0.1-3.0 μg mL-1of Cu(II) and correlation coefficient 0.9991. The percentage relative standard deviation was 2.5 for 10-replicate measurements and the limit of detection (LOD) was 0.1 μg mL-1. This system has been successfully applied to the determination of Cu(II) in wastewaters from electroplating industry with less reagents and samples consumption and diminutive waste generation. © 2006 Elsevier B.V. All rights reserved.